Tradisi Nyumbang: Implementasi Sosial Sustainability - Nanik Lestari; Falikhatun Falikhatun (Universitas Prasetiya Mulya, 2025)
This study examines the implementation of social sustainability principles through the Nyumbang tradition across various communities in Indonesia. It aims to explore how this local wisdom realizes social cohesion, inclusion, and welfare; analyze the underlying values and accountability mechanisms; and understand its contribution to contemporary social sustainability discourse. Using a phenomenological approach, data was collected through in-depth interviews with eleven informants from diverse ethnic and cultural backgrounds. The findings reveal that the Nyumbang tradition functions as an adaptive social system, playing a strategic role as a mechanism for resource redistribution, a binder of community cohesion, and a cultivator of social capital based on reciprocity, mutual cooperation, and trust. The practice also demonstrates flexibility in adapting to social changes, such as the shift in contribution forms from goods to money, without losing its essence of solidarity. The implications of this study affirm the importance of integrating local wisdom into sustainable social development frameworks. A limitation lies in the incomplete coverage of ethnic diversity, suggesting the need for further research with a broader comparative approach.